The Plausible Use of Mango (Mangifera indica) Peel Isoquercitrin as Adjuvant Therapy for Colorectal Cancer: Translating Research from Bench to Bedside - Habiburrahman, Muhammad; Sutopo, Stefanus; Rahadiani, Nur (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2023)
A deadly and debilitating disease, colorectal cancer (CRC), is rapidly becoming a significant threat to public health. However, current therapeutic approaches are still hampered by various side effects. Due to its benefits and remarkable apoptotic impact on cancer cells, plant-derived flavonoids now garner interest as candidates for cancer therapy. Isoquercitrin, a flavonoid commonly found in fruit plants, especially mangoes, is notable due to its ability to inhibit cancer development through various mechanisms. This review aims to highlight the use of isoquercitrin extracted from mango peels in inhibiting CRC carcinogenesis. A literature search was done on Pubmed, Proquest, and Google Scholar using inclusion and exclusion criteria, and a narrative review was synthesised using the evidence gathered. Validity assessment was done through the the Office of Health Assessment and Translation (OHAT) and Oxford Center for Evidence-Based Medicine (CEBM) critical assessment tools. Evidence suggested that isoquercitrin is promising as adjuvant therapy in CRC. It may inhibit overaccumulation of cytoplasmic β-catenin and its translocation into the nucleus, thus downregulating the expression of target proto-oncogenes leading to carcinogenesis of colon crypts. Isoquercitrin concentration in mango peel is abundant, 557.7 mg/kg in dried mango peel and 31.0 mg/kg in pure extracts. A pharmacology study approved that a daily intake of 5.4 mg/kgBW of isoquercitrin has an effective anticancer effect. This substance has good oral bioavailability and is well-tolerated but inhibits the metabolising enzymes CYP1A1 and CYP1B1. In conclusion, isoquercitrin is a potential adjuvant in inhibiting CRC growth with minimum costs and side effects.